Kemampuan Berpikir Kreatif Matematis Siswa SMP Pada Penerapan Model Pembelajaran Brain Based Learning - Anastasia Veranti Whisky Cahyani; Rohana; Ali Syahbana (Jurnal Inovasi Matematika, 2020)
This research investigates the influence of Brain-Based Learning Model to the students’ mathematical creative thinking. True Experimental Design method was used in this research because the subjects selected randomly. The subjects in this research were 50 students of seventh grade of SMP Xaverius 1 Palembang, there were 24 students of VII-A as an experimental group and 26 students of VII-I as a control group. The collecting data technique used a test that was analyzed using Independent Sample T-Test. Based on the result and discussion, it can be concluded that there is a significant influence between Brain-Based Learning models to mathematical creative thinking ability; this is affected in the teaching and learning process that carries out the variety of designs to reduce students’ boredom and challenge the students’ creativity.